Clinical impact of a routine, molecular, point-of-care, test-and-treat strategy for influenza in adults admitted to hospital (FluPOC): a multicentre, open-label, randomised controlled trial. Issue 4 (April 2021) - Clark, Tristan W; Beard, Kate R; Brendish, Nathan J; Malachira, Ahalya K; Mills, Samuel; Chan, Cathleen; Poole, Stephen; Ewings, Sean; Cortes, Nick; Nyimbili, Esther; Presland, Laura
Summary: Background: Diagnosis of influenza in patients admitted to hospital is delayed due to long turnaround times with laboratory testing, leading to inappropriate and late antiviral treatment and isolation facility use. Molecular point-of-care tests (mPOCTs) are highly accurate, easy to use, and generate results in less than 1 h, but high-quality evidence for their effect on management and clinical outcomes is needed. The aim of this study was to assess the clinical impact of an mPOCT on influenza detection, antiviral use, infection control measures, and clinical outcomes in adults admitted to hospital with acute respiratory illness. Methods: In this multicentre, pragmatic, open-label, randomised controlled trial (FluPOC), we recruited adults admitted to hospital with acute respiratory illness during influenza seasons from two hospitals in Hampshire, UK. Eligible patients were aged 18 years and older, with acute respiratory illness of 10 days or fewer duration before admission to hospital, who were recruited within 16 h of admission to hospital. Participants were randomly assigned (1:1), using random permuted blocks of varying sizes (4, 6 and 8), to receive mPOCT for influenza or routine clinical care (control group). The primary outcome was the proportion of patients infected with influenza who were treated appropriately with antivirals (neuraminidase inhibitors) within 5 days of admission. Safety was assessed in all patients. Secondary outcomes included time to antivirals, isolation facility use, and clinical outcomes. This study is registered with the ISRCTN registry, ISRCTN17197293, and is now complete. Findings: Between Dec 12, 2017, and May 3, 2019, over two influenza seasons, 613 patients were enrolled, of whom 307 were assigned to the mPOCT group and 306 to the control group, and all were analysed. Median age was 62 years (IQR 45–75) and 332 (54%) of 612 participants with data were female. 100 (33%) of 307 patients in the mPOCT group and 102 (33%) of 306 in the control group had influenza. 100 (100%) of 100 patients with influenza were diagnosed in the mPOCT group and 60 (59%) of 102 were diagnosed though routine clinical care in the control group (relative risk 1·7, 95% CI 1·7–1·7; p<0·0001). 99 (99%) of 100 patients with influenza in the mPOCT group were given antiviral treatment within 5 days of admission versus 63 (62%) 102 in the control group (relative risk 1·6, 95% CI 1·4–1·9; p<0·0001). Median time to antivirals was 1·0 h (IQR 0·0 to 2·0) in the mPOCT group versus 6·0 h (0·0 to 12·0) in the control group (difference of 5·0 h [95% CI 0·0–6·0; p=0·0039]). 70 (70%) of 100 patients with influenza in the mPOCT group were isolated to single-room accommodation versus 39 (38%) of 102 in the control group (relative risk 1·8 [95% CI 1·4–2·4; p<0·0001]). 19 adverse events occurred among patients with influenza in the mPOCT group compared with 34 events in the control group. No patients with influenza died in the mPOCT group and two (2%) died in the control group (p=0·16). Interpretation: Routine mPOCT for influenza was associated with improved influenza detection and improvements in appropriate and timely antiviral and isolation facility use. Routine mPOCT should replace laboratory-based diagnostics for acute admissions to hospital during the influenza season. Funding: National Institute for Health Research.